Into a world of hate : a journey among the extreme right - Ryan, Nick, 1968- (Routledge, 2004)
At a time of heightened fears over terrorism and Islam; as frustration builds with immigration and asylum; and as millions vote for far-right political parties, Into A World Of Hate is Nick Ryan's powerful odyssey into the world of the extreme right.